MANIFESTATION OF STRESS AND COPING CONCERNING PROFESSIONAL EXPERIENCE - Alifanoviene, Daiva; Sapelyte, Odeta; Orska, Rita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The paper focuses on the stress and coping exercised by pedagogues at mainstream schools in Lithuania. The main goal of the paper was to reveal significant contrast in manifestation of coping among different actors of educational process with regard to the diversity of their professional experience and spheres of activities. Quantitative empirical data were analysed by using descriptive and nonparametric statistical analysis (Mann-Whitney, Kruskall-Wallis tests). The empirical data (N=478) has shown that specialists of educational support tend to apply avoidance-oriented strategies with retreat more often than subject teachers. In addition, stress coping techniques applied by pedagogues are discussed with regard to their professional qualification.